Hydrogen bond and ligand dissociation dynamics in fluoride sensing of Re(I)-polypyridyl complex - Verma, Sandeep; Aute, Sunil; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry B, 2015)
Hydrogen bonding interaction plays an essential role in the early phases of molecular recognition and colorimetric sensing of various anions in aprotic media. In this work, the host-guest interaction between fac-[Re(CO)(3)Cl(L)] with L = 4-([2,2'-bipyridin]-4-yl)phenol and fluoride ions is investigated for the hydrogen bond dynamics and the changing local coordination environment. The stoichiometric studies using H-1 NMR and ESI-MS spectroscopies have shown that proton transfer in the H-bonded phenol-fluoride complex activates the dissociation of the CO ligand in the Re(I) center. The phenol-to-phenolate conversion during formation of HF2- ion induces nucleophilic lability of the CO ligand which is probed by intraligand charge transfer (ILCT) and ligand-to-metal charge transfer (LMCT) transitions in transient absorption spectroscopy. After photoexcitation, phenol-phenoxide conversion rapidly equilibrates in 280 fs time scale and the ensuing excited state [ReII(bpy(center dot-)-phenolate(-))(CO)(3)Cl]* undergoes CO dissociation in the ultrafast time scale of similar to 3 ps. A concerted mechanism of hydrogen cleavage and coordination change is established in anion sensing studies of the rhenium complex.